Publicidade em Feira de Santana: Paisagem, Imagem, Percepção e Linguagem - Silva, Marcelo João Alves da (2008)
This work aims to discuss the transformations occured in the urban Landscape and in the architecture in the commercial Center of Feira de Santana city caused by the influence of the Illuminated Advertising Signs from seventies to 2007. The research will be developed through analysis of photographs taken of Getúlio Vargas Avenue and Conselheiro Franco Street situated in the commercial center of the city made in different historical moments. An analytical and reflexive rereading based on semiotic, ergonomic and perceptive aspects will be done with the photographic sources observing the following elements: form, color, legibility, signification, composition, message and the visual manifestations.